Frailty and intellectual disability: A different operationalization?. Issue 1 (16th August 2013) - Evenhuis, Heleen; Schoufour, Josje; Echteld, Michael; Silverman, Wayne; Mailick, Marsha R.
<x xml:space="preserve">Abstract</x> Frailty is increasingly being recognized as a relevant health measure in older populations, associated with an increased risk of adverse health outcomes and care dependency. Because it is generally perceived that people with intellectual disabilities are "old" from age 50 onwards, frailty research in this group might lead to an understanding of factors, contributing to this perception. The development since the 1990s of conceptual and operational definitions of frailty has resulted in different approaches: biological (phenotype), multidimensional, and non‐specific deficit accumulation. All approaches consider disability a consequence rather than a cause of frailty. This may be different for long‐disabled populations, which would have consequences for validity of frailty measures. First research shows that the different approaches are applicable to study populations with intellectual disabilities as well. Frailty as defined by both the phenotypic and deficit accumulation approach appears to develop considerably earlier and is more severe in people with intellectual disabilities than in the general older population, supporting the notion of early aging. Before any clinical implications can be outlined, health outcomes (validity), causes, and prevention of frailty should be investigated. © 2013 Wiley Periodicals, Inc. Dev Disabil Res Rev 2013;18:17–21.